Biochemistry - U Satyanarayana and others; Chakrapani, U (Kolkata Elsevier ,Books and Allied Pvt Ltd, 2021)
SECTION ONE: CHEMICAL CONSTITUENTS OF LIFE Chapter 1: Biomolecules and the Cell Chapter 2: Carbohydrates Chapter 3: Lipids Chapter 4: Proteins and Amino Acids Chapter 5: Nucleic Acids and Nucleotides Chapter 6: Enzymes Chapter 7: Vitamins SECTION TWO: PHYSIOLOGICAL BIOCHEMISTRY Chapter 8: Digestion and Absorption Chapter 9: Plasma Proteins Chapter 10: Hemoglobin and Porphyrins Chapter 11: Biological Oxidation SECTION THREE: METABOLISMS Chapter 12: Introduction to Metabolism Chapter 13: Metabolism of Carbohydrates Chapter 14: Metabolism of Lipids Chapter 15: Metabolism of Amino Acids Chapter 16: Integration of Metabolism Chapter 17: Metabolism of Nucleotides Chapter 18: Mineral Metabolism SECTION FOUR: CLINICAL BIOCHEMISTRY AND NUTRITION Chapter 19: Hormones Chapter 20: Organ Function Tests Chapter 21: Water, Electrolyte and Acid-base Balance Chapter 22: Tissue Proteins and Body Fluids Chapter 23: Nutrition SECTION FIVE: MOLECULAR BIOLOGY AND BIOTECHNOLOGY Chapter 24: DNA-Replication, Recombination, and Repair Chapter 25: Transcription and Translation Chapter 26: Regulation of Gene Expression Chapter 27: Recombinant DNA and Biotechnology SECTION SIX: CURRENT TOPICS Chapter 28: Human Genome Project Chapter 29: Gene Therapy Chapter 30: Bioinformatics Chapter 31: Metabolism of Xenobiotics (Detoxification) Chapter 32: Prostaglandins and Related Compounds Chapter 33: Biological Membranes and Transport Chapter 34: Free Radicals and Antioxidants Chapter 35: Environmental Biochemistry Chapter 36: Insulin, Glucose Homeostasis, and Diabetes Mellitus Chapter 37: Cancer Chapter 38: Acquired Immunodeficiency Syndrome (AIDS) SECTION SEVEN: BASICS TO LEARN BIOCHEMISTRY Chapter 39: Introduction to Bioorganic Chemistry Chapter 40: Overview of Biophysical Chemistry Chapter 41: Tools of Biochemistry Chapter 42: Immunology Chapter 43: Genetics Appendices Answers to Self-assessment Exercises Abbreviations used in this Book Origins of Important Biochemical Words Common Confusables in Biochemistry Practical Biochemistry-Principles Clinical Biochemistry Laboratory Case Studies with Biochemical Correlations Index
Keywords: Biochemistry